Xenon Exerts Neuroprotective Effects on Kainic Acid-Induced Acute Generalized Seizures in Rats via Increased Autophagy - Zhu, Wei; Zhu, Jianguo; Zhao, Shengfa; Li, Jieqing; Hou, Dianjun; Zhang, Yurong; Sun, Hongliu (Frontiers in Cellular Neuroscience, 2020)
Xenon has been shown to have neuroprotective effects and is clinically used as a favorable safe inhalation anesthetic. We previously confirmed the neuroprotective effects of xenon treatment in epileptic animals. However, the mechanism underlying these protective effects remains unclear. We aimed to assess the effects of xenon inhalation on autophagy in neuronal injury induced by acute generalized seizures. Kainic acid (KA) was injected into the lateral ventricle of male Sprague-Dawley rats to induce acute generalized seizures. Next, the rats were treated via inhalation of a 70% xenon/21% oxygen/9% nitrogen mixture for 60 min immediately after KA administration. The control group was treated via inhalation of a 79% nitrogen/21% oxygen mixture. Subsequently, two inhibitors (3-methyladenine or bafilomycin A1) or an autophagy inducer (rapamycin) were administered, respectively, before KA and xenon administration to determine the role of autophagy in the protective effects of xenon. The levels of apoptosis, neuronal injury, and autophagy were determined in all the rats. Xenon inhalation significantly attenuated the severity of seizure-induced neuronal injury. Increased autophagy accompanied this inhibitive effect. Autophagy inhibition eliminated these xenon neuroprotective effects. A simulation of autophagy using rapamycin recapitulated xenon’s protective effects on KA-induced acute generalized seizures in the rats. These findings confirmed that xenon exerts strong neuroprotective effects in KA-induced acute generalized seizures. Further, they indicate that increased autophagy may underlie the protective effects of xenon. Therefore, xenon and autophagy inducers may be useful clinical options for their neuroprotective effects in epileptic seizures.